Secagem de celulases de origem fúngica por spray-drying - Shiota, Viviane Moriya [UNESP] (2014)
This work aimed to provide technological treatment to enzymatic extract rich in endoglucanase, obtained by solid state culture using the fungus Myceliophtora thermophila M77, through spray-drying. Operational parameters and adjuvants were varied in order to obtain stable enzymes with high activities during storage. The experiments were divided into adjuvant discrimination, optimization of the drying conditions, storage of the raw enzymatic extract (REE) and powders, evaluation of drying on the physical-chemical characteristics of the endoglucanase, and powder morphology. Statistical experimental designs were used to evaluate the effect of the variables exit air temperature, solution flow rate, proportion REE/adjuvant, and total solid content on the enzyme activity retention and powder moisture content. The adjuvant Arabic gum was selected from the discrimination assays. From the optimization experiments, it was determined that the lower flow rate and air exit temperature resulted in the highest enzyme activity retention, while low temperature and solution flow rate resulted in the lowest retention. The total solid concentration was not statistically significant. The powders produced in the Best and in the worst drying conditions were stored at room temperature and under refrigeration and the enzymatic activity was measured at 15 days intervals. The statistical analysis did not show any difference in the enzymatic activity retention after long periods of storage for both drying conditions and both storage alternatives. The influence of temperature and pH on the enzyme activity was also investigated before and after the drying process, and it was noticed that these physical-chemical properties were not affected by the adjuvants and by the drying process. The morphology of the powders, obtained using the inert gas adsorption method, indicated that the powder obtained under the worst drying condition presented specific superficial area twice ...